Prices of vegetables and fruits in Ethiopia: Trends and implications for consumption and nutrition - Bachewe, Fantu Nisrane; Minten, Bart (International Food Policy Research Institute, 2021)
We study price behavior of vegetables and fruits in Ethiopia over the 15 year period from 2005 to 2019 based on large-scale retail and producer price datasets. This is an important topic given the importance of prices for consumption decisions for these nutritious crops. A number of notable findings come from the analysis. First, prices are rapidly increasing both in real terms and when compared to cereals. At the end of the study period in 2019, vegetables and fruits in real terms were significantly more expensive than 15 years earlier. Especially green leafy vegetables show a significant price rise, likely because few high-yielding varieties of these vegetables have been made available and adopted by producers. Second, part of the rise in prices is explained by increased marketing margins. To understand what accounts for these increases in the marketing margins for fruits and vegetables requires more research, as they contrast with stable or declining margins seen for other food crops over the study period. Third, we see significant seasonality in vegetable prices that is mostly driven by supply factors, but also by demand shifts due to increased demand in fasting periods. Fruit prices do not show such high seasonal variation, however. Fourth, there is significant spatial price variation in the country – vegetable prices are 60 percent more expensive in lowland regions than in the Amhara region, where vegetables are cheapest. Fruit prices in the lowlands are double the prices in the major producing area, the Southern Nations, Nationalities, and Peoples' (SNNP) region.